Lifebox: A Global Patient Safety Initiative. Issue 12 (15th June 2016) - Enright, Angela; Merry, Alan; Walker, Isabeau; Wilson, Iain
Abstract : The safety of anesthesia was dramatically improved by the introduction of pulse oximetry. This technology was rapidly adopted by anesthesiologists and made a standard of practice in many countries. In 2007, during development of the Surgical Safety Checklist, the World Health Organization recommended a pulse oximeter as a monitor for all patients undergoing anesthesia. However, clinicians in low- and middle-income countries lack access to basic anesthesia equipment, including pulse oximeters. The Lifebox Foundation was formed to determine how a suitable oximeter could be made available to anesthesia providers in these countries. Almost 11, 000 oximeters have been delivered in 90 countries, with education courses completed in over 50 countries.